Fractures in patients with chronic kidney disease - S. L. Dudar (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. Despite rapid progress in improving dialysis technology in recent years, the mortality of patients treated with renal replacement therapy remains quite high. Mineral and bone disease is omnipresent in patients with chronic kidney disease (CKD) and leads to a diverse range of clinical manifestations, including bone pain and fractures. Mineral bone disorders (MBD), as well as changes in bone structure, develop at the beginning of CKD. Osteoporosis can progress according to declining of the glomerular filtration rate and contribute to the deterioration of bone strength resulted in a high risk of fracture. In CKD patients, the most common are hip fractures, femur, humerus, compression fractures of the vertebrae and pelvic fractures. CKD-MBD is characterized by disorders of calcium, phosphate, parathyroid hormone and/or vitamin D metabolism, as well as, bone regeneration, mineralization, volume, linear growth and strength violation, calcification of blood vessels, or other soft tissues. Medications that correct systemic mineral metabolism can improve bone histology in patients with CKD. However, clinical and biochemical targets used in clinical practice remain controversial, resulting in an undermanagement of bone fragility.  The clarifying of the appropriateness of medicines that act directly on the bone or affect the mineral and hormonal metabolism could be a promising strategy to prevent pathological fractures due to fragility among CKD patients.